The practical handbook of perioperative metabolic and nutritional care - Correia, M. Isabel T. D. (Academic Press, 2019)
The Practical Handbook of Perioperative Metabolic and Nutritional Care focuses on topics ranging from the history of surgery and metabolism, to the organic response to stress. Based on clinical processes, the author explores screening, assessment and the impact of nutritional status on outcomes, in addition to investigating nutritional requirements, including macronutrients and micronutrients. Chapters examine wound healing and metabolic and nutritional surgical preconditioning, including coverage of preoperative counseling, preoperative nutrition and preoperative fasting. In addition, physical exercise is addressed, as is nutritional therapy in the form of oral supplements, and enteral and parenteral approaches. Additional topics explored include nutrition therapy complications and immunomodulatory nutrients, pro, pre and symbiotics, postoperative oral, enteral and parenteral nutrition, enteral access, vascular access, fluid therapy, and more. Addresses preoperative metabolic and nutritional preparation for surgeryExplores processes for intra and postoperatively assessing metabolic and nutritional state to ensure patient progressContains content based on clinical processIncludes related case studies that enhance the subject matter